Cyclooxygenase-2 expression in cervical squamous cell carcinoma: the significance of expression in neoplastic cells within the lymphovascular space - Settakorn J. (2014)
Cyclooxygenase-2 (COX-2) activity is related to the development and progression of cervical cancer. Previous studies have shown that COX-2 expression in early stage (stage IB-IIA) cervical squamous cell carcinoma is associated with lymph node metastasis in tumors with lymphovascular space invasion (LVSI), and that COX-2 expression may facilitate lymph node metastasis after LVSI occurs. In this study, we evaluated whether COX-2 expression of neoplastic cells within lymphovascular spaces (tumor emboli) would provide additional prognostic information.